Preparation, characterization and in vitro biological evaluation of (1:2) phenoxodiol-β-cyclodextrin complex. (1st June 2017) - Yee, Eugene M.H.; Hook, James M.; Bhadbhade, Mohan M.; Vittorio, Orazio; Kuchel, Rhiannon P.; Brandl, Miriam B.; Tilley, Richard D.; Black, David StC; Kumar, Naresh
Highlights: Characterization of a 1:2 stoichiometry phenoxodiol-β-cyclodextrin complex. The best 'ship-in-a-bottle' case of guest-β-cyclodextrin complex crystal structure. Increased aqueous solubility of phenoxodiol by 9 times. Improved anti-proliferative activity against cancer cells and decreased toxicity against normal cells. Abstract: Phenoxodiol is an isoflavone analogue that possesses potent anticancer properties. However, the poor water solubility of phenoxodiol limits its overall efficacy as an anticancer agent. To overcome this, β-cyclodextrin was used to encapsulate phenoxodiol. The phenoxodiol-β-cyclodextrin complex was prepared via a modified co-evaporation method and characterized by 1 H NMR and X-ray crystallography, revealing a 1:2 stoichiometry. The 2D ROESY NMR spectroscopy suggested the limited motion of phenoxodiol within the cavity of β-cyclodextrin while the X-ray crystal data displays by far the best 'ship-in-a-bottle' case of 1:2 inclusion complex. The aqueous solubility of the phenoxodiol in β-cyclodextrin had improved and the in vitro biological evaluation revealed enhanced anti-proliferative activity against three cancer cell lines. Additionally, the toxicity of the complex against normal human cell line was 2.5 times lower. These data indicates that the encapsulation of phenoxodiol into β-cyclodextrin leads to an improvement in its overall water solubility and biological activity.